Ultrasonographically Documented Response in a Case of Ovarian Cyst: A Case Report (Advancements in Homeopathic Research, 2022)
A case of follicular cyst in left ovary together with bulky uterus having ultrasonographic documentation of improvement of both the problems simultaneously after treatment is presented. The basis of prescription and details of periodic assessment are provided. The likelihood of improvement attributable to homoeopathic treatment is also discussed.The ‘take-away’ lesson from the case is homoeopathic treatment is capable to reverse the pathological changes, evenin minimum dose, if the prescription is done strictly following the basic principles of Homoeopathy.
Keywords: Ovarian cyst; Bulky uterus; Homoeopathy; Natrum muriaticum; Ultrasonography; HOM-CASE